A crosslinked β-cyclodextrin polymer used for rapid removal of a broad-spectrum of organic micropollutants from water. (1st December 2017) - Wang, Zhanghui; Zhang, Peibin; Hu, Fan; Zhao, Yifan; Zhu, Liping
Highlights: More than 99% micropollutants in water were removed by flowing the feed water through the column of β-cyclodextrin polymers. The optimal β-cyclodextrin polymer can remove 90% of BPA equilibrium adsorption amount within 1 min. The maximal adsorption capacity was 113.0 mg of bisphenol A per gram of β-cyclodextrin polymer. β-CDP shows good reproducibility after a simple and mild ethanol cleaning. Abstract: Organic micropollutants in aquatic environment such as plasticizer, pesticide and pharmaceuticals, have posed a serious threat to human health and are emerging as a great challenge to humanity. Traditional water treatment techniques fail to achieve high removal efficiency for low concentration of organic micropollutants. Here we demonstrate a water-insoluble crosslinked β-cyclodextrin (β-CD) polymer able to remove a broad-spectrum of organic micropollutants from water by rapid adsorption. A family of β-CD polymers (β-CDPs) were synthesized by nucleophilic aromatic substitution of β-CD hydroxyl groups and 4, 4′-difluorodiphenylsulfone. The β-CDPs were used to adsorb various organic micropollutants in water by static or dynamic adsorption process. It was found that more than 99% micropollutants in water were removed by flowing the feed water through the column of β-CDPs. The results of static adsorption experiments indicated the adsorption process was fast and the adsorption capacity was very high (the maximal value was 113.0 mg of bisphenol A per gram of β-CDP). The adsorption process was fitted well with the quasi-second-order kinetics and the Langmuir isothermal adsorption model, suggesting that it is mainly a chemical adsorption of monolayer. The water-insoluble characteristic of the β-CDPs is convenient for their separation from the treated solution after adsorption saturation for regeneration and reuse. The adsorption ability of β-CDPs was kept nearly unchanged after five filtration-regeneration cycles.